2010
DOI: 10.1249/mss.0b013e3181b88d37
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Training for Sports Injury Prevention

Abstract: On the basis of the results of seven high-quality studies, this review showed evidence for the effectiveness of proprioceptive/neuromuscular training in reducing the incidence of certain types of sports injuries among adolescent and young adult athletes during pivoting sports. Future research should focus on the conduct of comparative trials to identify the most appropriate and effective training components for preventing injuries in specific sports and populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
253
0
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(270 citation statements)
references
References 53 publications
7
253
0
10
Order By: Relevance
“…Balance training has commonly been used to improve performance and prevent injury in an active population. 32 Training focuses on heightening the sensorimotor system for more efficient automatic muscular responses to maintain postural control.…”
Section: Discussionmentioning
confidence: 99%
“…Balance training has commonly been used to improve performance and prevent injury in an active population. 32 Training focuses on heightening the sensorimotor system for more efficient automatic muscular responses to maintain postural control.…”
Section: Discussionmentioning
confidence: 99%
“…54,63 The NNT analysis performed in these controlled trials revealed that 7 to 9 players needed to be treated with an injury-prevention program to prevent 1 ankle injury. A systematic review by Hubscher et al 167 suggested a similar reduction in risk (36%) of ankle sprains using comparable neuromuscular-control training regimens. The interventions in these studies included single-legged-stance balance training, balance training with additional perturbation, balance training with upper extremity movements or tasks, and dynamic jumping activities with a balance component.…”
Section: Prevention Of Lateral Ankle Sprains: Prophylactic Exercisementioning
confidence: 96%
“…Systematic reviews suggest that randomised trials of strength and balance exercise (proprioceptive or neuromuscular training) programmes can reduce rates of lower extremity injuries overall, acute knee injuries, and ankle sprain. 42 The academic specialty of sports injury epidemiology, prevention, and health economics is one that is emerging in this century.…”
Section: Injury Risk In Sportmentioning
confidence: 99%